IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TAI ( TEAM ASSISTED INDIVIDUALIZATION ) DALAM PEMEBLAJARAN FIQIH PADA SISWA MTS MUHAMMADIYAH 06 BANYUTENGAH TAHUN AJARAN 2015/2016 - Nugra Heny Apriliah; Muyasaroh muyasaroh (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Muhammadiyah Gresik, 2015)
THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TEAM ASSISTED INDIVIDUALIZATION IN LEARNING FIQH AT THE JUNIOR HIGH SCHOOL STUDENTS OF 06 BANYUTENGAH, Essay: Faculty of Islamic Religious Education of Muhammadiyah Gresik University, 2016. The purpose of this thorough is the low interest in learning and lack of cooperation each other in the class so that make the state of the class is not condusive, to solve the problem doing this research to know the implementation of the Team Asssisted individualizataion process, the obstacles of that faced, and the effort will be undertaken for reach the purpose. This research was conducted at the Junior High school of Muhammadiyah 06 Banyutengah. The subject of the research is student in grade VIII the school years of 2016/2017 with the number of student 21. The data collected in the form of Observation result, interview and documentation. Data analysis techniques used is perform data reduction, presentation and drawing conclusions. The result of this study obstacles encountered in the application of cooperative learning models of the Team Assisted Individualization is influential in the less maximal application of this model, however with thw effort of teachers, the learning process can run well in the line expectations.